Decision-support challenges in the chemical-pharmaceutical industry: Findings and future research directions. (4th March 2020) - Marques, Catarina M.; Moniz, Samuel; de Sousa, Jorge Pinho; Barbosa-Povoa, Ana Paula; Reklaitis, Gintaras
Highlights: New reference framework to assist in the development of optimization-based decision-support models. Definition of the expected new pharmaceutical paradigm and its main supply chain components. Thorough literature review evidencing the structure of the planning problems in the pharmaceutical industry. A novel view of the industry's drivers, enablers, and challenges – the impact matrix. Main findings reveal an overall misalignment of the current research with the main trends driving the industry. Abstract: The chemical-pharmaceutical sector is facing an unprecedented fast-changing environment, with new market and technological trends impacting the companies' operational strategies. Managing the pharmaceutical supply chain (PSC) operations is, therefore, ever more complex and challenging. The goal of this work is to present a comprehensive overview of the current state of the industry and research developments; and then, to develop a new decision-making reference framework to assist in the creation of optimization-based decision support models. This will be achieved through a multi-perspective analysis that encompasses strategic and tactical planning decision-making, in the current and future business context of the chemical-pharmaceutical industry. The findings reveal a lack of research addressing the most prominent trends currently driving this sector, such as patient centricity or new technological developments, thus highlighting the disruptive nature of the expected changes in a highly conservative industry.